Colliding branes and big crunches - Omotani, John; Saffin, Paul M.; Louko, Jorma (American Physical Society, 2011)
We examine the global structure of colliding domain walls in AdS spacetime and come to the conclusion that singularities forming from such collisions are of the big-crunch type rather than that of a black brane.